Quem tem AIDS se cuida: uma pesquisa qualitativa sobre o autocuidado - Müller, Letícia Possebon (Universidade do Vale do Rio dos Sinos, 2010)
To analyze the perceptions and self-care practices of people living with AIDS, followed at a specialized secondary level, at a hospital in Porto Alegre-RS. METHODS: a semi-structured interview was used as social research tool in this qualitative and analytical study. Twenty-one individuals over age 18, diagnosed with HIV/AIDS after 1996 (year that the universal distribution of antiretroviral began), followed at a specialized health care facility in the city of Porto Alegre, during September and October 2009, were interviewed. Data analysis was done by categorizing the interviews from the regularities and peculiarities in the speech of interviewees. RESULTS: The diagnosis of HIV/AIDS changed the way people think about health and disease, AIDS has become a biographical episode in their lives. AIDS becomes a marker for self-care, where care has different meanings and practices. The body, food and the environment become the targets of greatest concern because of prejudice. The self-care (before diagnosis) starts to be sought and legitimized in health services, where the use of medication, periodic exams and the interaction with health professionals acquire meanings. Issues of gender and time of diagnoses interfere with self-care. The actions of self-care are solidary and go beyond the others? care. CONCLUSIONS: Based on the analysis of the interviews, it is possible to indicate that care is established at different levels and within different contexts and relationships. The self ?care, thus, depends on the place that AIDS occupies in the life of each person, noting that the disease is a social construction. AIDS works, for the interviewed individuals, as a marker for the care in their trajectories. Care is enrolled in different levels, within and outside the health service, is based on the individual but is also collective since it is established in the context of relationships with others (family, friends, coworkers) and with the environment.
Keywords: Saúde coletiva; Autocuidado; Saúde; Aids; Serviços de saúde; Vulnerabilidade; Self-care; Health; Health services; Vulnerability; ACCNPQ::Ciências da Saúde::Saúde Coletiva